Visualizing textual similarity of Shakespearean suspect texts: An examination of the Henry VI plays. - Kim, Heejin (Digital Scholarship in the Humanities, 2021)
The relationship between Shakespeare's First Folio and early printings, published in his lifetime, has been a matter of dispute for centuries. A computer program that I have developed visualizes the fluctuating quality of textual correspondences between Folio texts, Henry the Sixth , Part Two and Three , and texts that have been suspected as memorial reconstructions of the Folio, The First Part of the Contention and The True Tragedy of Richard Duke of York. The memorial reconstruction hypothesis assumes increased similarity between the two texts when an alleged actor–reporter is on the stage or speaking and vice versa. The visualization of similarity between two texts, based on the Dice similarity metric, does not show a strong association between the fluctuation of similarity and actor–reporter factors, which challenges the memorial reconstruction hypothesis on statistical grounds. In addition, the distribution of line-by-line similarity scores suggests scene division is a considerable explanatory factor for fluctuating similarity, which is not inexplicable, considering the practice of collaborative writing in the early modern playhouse.